Non-timber Forest Products in Bu Gia Map: Local Use and Sustainable Management - Dinh, Thanh Sang (Jurnal Manajemen Hutan Tropika, 2025)
Non-timber forest products (NTFPs) in Bu Gia Map National Park (BGMNP) have played a critical role in local livelihood. Thus, the park resources have been threatened by local harvesting. Yet, the local perspective of the NTFP utilization between indigenous ethnic minorities (IMs) and Kinh peoples (KPs) has been poorly understood. Besides, in order to analyze the resource use between the IMs and the KPs, the “walk-in-the-wood” method and the participatory rural appraisal (PRA) were employed. This paper revealed that the local NTFP utilization gradually shifted from purely self-consumption to more income generation (p-value = 0.000 < 0.05). Besides, the IMs relied much upon the NTFPs, whereas the KPs were less dependent upon these resources. The IMs harvested these resources for more subsistence related to their traditional and basic needs than those KPs. Based on the local findings, the institutional management strategies in BGMNP should emphasize resource utilization patterns, human capital empowerment, and group-based arrangements. Likewise, group-based arrangements in BGMNP would play an important role in the local livelihood improvement and the sustainable park development.